The Quality of Financial Statements with Human Resource Competence as Moderating Variables - Diana Frederica; Villery Cristina; Agus Munandar (Universitas Pendidikan Ganesha, 2023)
This study aims to examine the effect of accounting information systems, internal audit and human resource competencies on the quality of financial statements. This study also tested the variable of human resource competence as a moderating variable. The population in this study are accountants and internal auditors who work in companies domiciled in DKI Jakarta. The sampling technique used is convenience sampling. The data collected and can be processed are as many as 100 respondents. The data of this study were analyzed by multiple linear regression method. The results of this study indicate that the application of accounting information systems, the role of internal audit and the competence of human resources have a positive effect on the quality of financial statements. However, the competence of human resources does not strengthen the influence of accounting information systems and internal audit on the quality of financial statements. The contribution of this research is as a benchmark for companies to be able to optimize the use of accounting information systems, the importance of the role of internal auditors, and human resources owned must be competent to produce quality financial statements. Quality resources in terms of knowledge and skills if not balanced with good ethics, then do not guarantee the quality of good financial statements.